A Holistic Approach to Character Education: Integration of Governance, Islamic Values, and School Culture - Ayu, Salsabilla Martina; Kosasih, Aceng; Hermawan, Wawan; Rosidin, Asep; Amatullah, Zulfa Afifah (Southeast Asian Journal of Islamic Education, 2024)
This study investigates a comprehensive approach to strengthening character education by integrating governance, Islamic values, and school culture in primary education. Conducted over one year in nine public elementary schools in West Bandung Regency, West Java, Indonesia, this study employed a mixed-methods approach, combining qualitative descriptive and descriptive quantitative designs. Qualitative data were collected through interviews, observations, and document analysis, while quantitative data were obtained via questionnaires to evaluate the implementation of governance programs in character education. The study involved nine principals and 135 teachers as participants, with students observed during program implementation. Data analysis was conducted using thematic analysis for qualitative data, identifying recurring themes and patterns related to governance and school culture. Descriptive statistics, including scoring and average calculations, were used to assess the implementation of governance programs for quantitative data. The findings reveal that well-structured governance, characterized by clear policies and coherent program designs, is pivotal in fostering a school culture conducive to character development. The integration of Islamic values, including Shiddiq (truthfulness), Amanah (trustworthiness), Tabligh (effective communication), and Fathonah (wisdom), significantly enhances these efforts. Active community engagement and continuous evaluation were also identified as critical factors. This study underscores the necessity of a holistic governance framework that involves all stakeholders, providing actionable insights to enhance character education in elementary schools and develop students who excel academically while upholding strong moral integrity.